2018
DOI: 10.1177/1933719117716778
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Is Associated With Sexual Pain in Women With Endometriosis

Abstract: Endometriosis is present in 1 in 10 reproductive-age women, and half experience deep dyspareunia (pelvic pain with sexual intercourse). Our objective was to investigate nerve growth factor (NGF) and its receptors (TrkA/p75NTR) in endometriosis-associated deep dyspareunia. A total of 32 women with endometriosis in the posterior pelvic compartment (cul-de-sac/uterosacrals) were included, either with (n = 17) or without (n = 15) deep dyspareunia symptoms confirmed by endovaginal ultrasound-assisted palpation on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Some of these cases overlap with our previous studies: 23 SUP cases were previously used for work on nerve density and nerve growth factor in endometriosis;[10, 11] and 7 DIE cases, 7 OMA cases, and 6 UE cases have been previously used for studies on HOXB4 in endometriosis [12].…”
Section: Methodsmentioning
confidence: 96%
“…Some of these cases overlap with our previous studies: 23 SUP cases were previously used for work on nerve density and nerve growth factor in endometriosis;[10, 11] and 7 DIE cases, 7 OMA cases, and 6 UE cases have been previously used for studies on HOXB4 in endometriosis [12].…”
Section: Methodsmentioning
confidence: 96%
“…Emerging evidence has suggested a critical role for NTs in uterine physiology and endometrial pathology (Barcena de Arellano et al , 2013; Wessels et al , 2014). The immunointensity of NGF and TrkA was higher in both the endometriotic stroma and epithelium obtained from women with endometriosis and deep dyspareunia than that in those obtained from women with endometriosis without deep dyspareunia, indicating that NGF signaling may play an important role in endometriosis-associated sexual pain (Peng et al , 2018). A clinical study demonstrated that women with endometriosis had higher levels of NGF in their FF than did patients with male factor infertility (Buyuk and Seifer, 2008).…”
Section: Roles For Nts In Ovarian Pathology and Diseasesmentioning
confidence: 99%
“…Pelvic adhesions are common in endometriosis, especially with deep infiltrating endometriosis, and may also contribute to deep dyspareunia [10,11]. With respect to superficial peritoneal endometriosis, one study showed that superficial endometriotic lesions of the pouch of Douglas in women with deep dyspareunia had increased density of nerve bundles, as well as elevated immune-intensity of nerve growth factor and its TrkA receptor, compared to patients with endometriotic lesions of the same anatomic location but without deep dyspareunia [12,13]. These findings suggest that local neurogenesis around endometriosis may also contribute to pain with intercourse [12,13].…”
Section: Endometriosismentioning
confidence: 99%
“…With respect to superficial peritoneal endometriosis, one study showed that superficial endometriotic lesions of the pouch of Douglas in women with deep dyspareunia had increased density of nerve bundles, as well as elevated immune-intensity of nerve growth factor and its TrkA receptor, compared to patients with endometriotic lesions of the same anatomic location but without deep dyspareunia [12,13]. These findings suggest that local neurogenesis around endometriosis may also contribute to pain with intercourse [12,13]. Local inflammation via cyclooxygenase-2 (COX-2)-prostaglandin E2 (PGE2)-estrogen and other inflammatory positive feedback loops may also contribute to deep dyspareunia in endometriosis [14].…”
Section: Endometriosismentioning
confidence: 99%